Implementation of Education System Evaluation Policy through the Utilization of Education Report Cards in Junior Secondary Schools - Siska Purnama Sari; Yanhar Jamaluddin; Beby Masitho Batubara (Ali Institute of Research and Publication, 2026)
The Education Report Card supports education system evaluation and data-based planning at the school level. This study analyzes its implementation at SMP Negeri 1 Sawit Seberang and identifies supporting and inhibiting factors. A descriptive qualitative approach was employed, with data collected through interviews, observation, and documentation involving school stakeholders. Data were analyzed using George C. Edwards III’s policy implementation framework: communication, resources, disposition, and bureaucratic structure. The findings show that the Education Report Card has been used for school reflection, planning, and program development, although its utilization remains suboptimal. Supporting factors include internal communication, stakeholder commitment, planning documents, and the school quality assurance team. Inhibiting factors include uneven teacher understanding, limited communication with parents, inadequate facilities, and flood-related damage to learning resources. Strengthening data literacy, teacher capacity, stakeholder communication, and educational facilities is therefore necessary to optimize the Education Report Card for school improvement planning.